Analisis Kosentrasi Total Solid Particulate (TSP) dan Karbon Monoksida (CO) Pada Ruas Jalan Utama di Kota Kendari - Sirajuddin Sarah Soraya; Sumarlin Marlin; Rosdiana Rosdiana (LP3M Universitas Muhammadiyah Kendari, 2021)
This study analyzed the concentrations of TSP and CO at 2 different sites in Kota Kendari. Measurement of TSP levels at the site I, Jl. MT Haryono, the highest concentration occurred in the morning (79 g/Nm3) compared to midday (51 g/Nm3) and in the afternoon (46 g/Nm3). Judging from the quality standards based on PP No. 41 of the year 1999, the concentration of TSP and CO on Jl. MT Haryono has not exceeded the quality standard. However, according to PP No. 22 of the year 2021, the CO level has reached the quality standard threshold. At site II, the TSP level at Jl. The highest Achmad Yani occurred in the morning at 63 g/Nm3 compared to midday (28 g/Nm3) and in the afternoon (35 g/Nm3) while CO levels in the morning, afternoon, and evening remained stable at 12,000 g/Nm3. Based on PP No. 41 of the year 1999, the concentrations of TSP and CO in ambient air on Jl. Ahmad Yani has not exceeded the quality standard, but if it is reviewed based on PP no. 22 of the year 2021, CO levels have exceeded the quality standard threshold. Physical factors (temperature, wind speed, and humidity) and anthropogenic factors such as motorized vehicle traffic are maybe contributions.